SEMINAR PEMANFAATAN APLIKASI PHOTOMATH UNTUK MEMPERMUDAH PEMBELAJARAN MATEMATIKA DI SD BUSTANUL HUDA SURABAYA - Zaehol Fatah; Rofiatul Aulia (Jurnal Padamu Negeri, 2026)
The mathematics learning process at the elementary school level still faces many challenges, particularly the lack of enthusiasm for learning and the obstacles experienced by students in understanding abstract mathematical concepts. Bustanul Huda Elementary School, Surabaya, is one of the elementary schools facing these challenges, where some students face challenges in working on math problems independently. This activity aims to introduce and provide training on the use of the Photomath application. Photomath as a learning aid for students at Bustanul Huda Elementary School, Surabaya. The implementation method uses a participatory and demonstrative approach consisting of preparation, implementation, and evaluation stages. The preparation stage is carried out through an initial survey, coordination with the school, and the preparation of seminar materials and training modules. The implementation stage includes a seminar on introducing mathematics learning technology, a workshop on using the Photomath application, and guided independent practice with the assistance of a community service team. The evaluation stage is carried out through a participant satisfaction questionnaire and observations during the activity. This activity was attended by 20 fifth and sixth grade students at Bustanul Huda Elementary School, Surabaya. The results of the activity stated that the use of the Photomath application has a positive influence on the mathematics learning process. 87% of participants stated that the Photomath app helped them understand how to solve math problems, 79% felt their motivation to learn increased, and 91% stated they would continue using the app as a tool in their math learning. Thus, the Photomath app can be used as a supporting learning tool that helps students understand mathematical ideas in a more visual, interactive, and independent way.